2021
DOI: 10.1186/s12977-020-00543-z
|View full text |Cite|
|
Sign up to set email alerts
|

Human T-cell leukaemia virus type 1 associated pulmonary disease: clinical and pathological features of an under-recognised complication of HTLV-1 infection

Abstract: The lung is one of several organs that can be affected by HTLV-1 mediated inflammation. Pulmonary inflammation associated with HTLV-1 infection involves the interstitium, airways and alveoli, resulting in several clinical entities including interstitial pneumonias, bronchiolitis and alveolitis, depending on which structures are most affected. Augmentation of the inflammatory effects of HTLV-1 infected lymphocytes by recruitment of other inflammatory cells in a positive feedback loop is likely to underlie the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 114 publications
0
23
0
1
Order By: Relevance
“…Although recent publications, including a systematic review, have suggested a causal relation between HTLV-1 and the development of lung injury [ 10 , 20 ], there are no studies which show the evolution of lung disease in HTLV-1 infected patients. This may be due to the lack of cohort studies needed to follow the evolution of these pulmonary symptoms in carrier patients or monitor infection progress in asymptomatic patients, making it impossible to establish a justifiable causal relationship between the virus and the emergence of lung injuries or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent publications, including a systematic review, have suggested a causal relation between HTLV-1 and the development of lung injury [ 10 , 20 ], there are no studies which show the evolution of lung disease in HTLV-1 infected patients. This may be due to the lack of cohort studies needed to follow the evolution of these pulmonary symptoms in carrier patients or monitor infection progress in asymptomatic patients, making it impossible to establish a justifiable causal relationship between the virus and the emergence of lung injuries or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of non‐infectious pulmonary disease in ATLL patients, abnormal chest CT findings are diverse, including ground‐glass opacities, bronchiectasis, centrilobular nodules and interlobular septal thickening. 4 The incidence of abnormal findings was higher in aggressive ATLL than in indolent ATLL. 5 In the present case, aggressive ATLL was suspected because of the extensive ground‐glass opacities on chest CT and abnormal T lymphocytes and flower cells in peripheral blood.…”
Section: Discussionmentioning
confidence: 92%
“…Prospective studies are necessary to more accurately define the risk of developing disease entities that is associated with a given PVL. However, ensuring that participants are correctly classified at baseline will be extremely difficult, particularly for those with bronchiolitis and early HTLV-1 associated pulmonary disease [ 33 ], and neurological disease not fulfilling HAM criteria [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%